Literary Tradition in Discourse of Abdülhak Şinasî Hisar - Ramić, Alena (Prilozi za orijentalnu filologiju, 2017)
Abdülhak Şinasi Hisar, a writer who gained wide recognition in 1930s, the period of blossom in the modem Turkish literature, was one of the rare writers who cherished both the classical approach and traditional esthetics in their opuses. Although renown as a novelist and a writer of memories, a great part of his work was composed of essays about literature. It is the way these essays were written, filled with subjectivity and poetic expressions and, therefore, not eligible to be defined as literary criticism in the modern sense, that laid the basis for the ideological framework of his works, marked with resistance in face of modernity. Hisar's understanding of art emphasized the style accepting it as the most important criteria for the evaluation of quality in a literary composition. As a consequence he neglected borders that separate genders in literature, the fact that left a strong trace in his creativity. In light of Turkish literary tradition this paper seeks to analyze Hisar’s traditional approach to the issue of both gender and characteristics of style in three of his the most famous books: Ali Nizami Beyin Alafrangalığı ve Şeyhliği, Çamlıcadaki Eniştemiz and Fahim Bey ve Biz.